2017
DOI: 10.3906/fiz-1603-24
|View full text |Cite
|
Sign up to set email alerts
|

Diluted magnetic semiconductor: structure, size and shape, and magnetic properties

Abstract: Abstract:In dilute magnetic metallic alloys, spin exchange interactions among transition metal ions at the ZnO structure cause changes in the magnetic properties of the nanocrystals depending on size and shape. The effect of size and shape on the structural and magnetic properties of semiconductors, using atomistic spin calculations, is the main topic of this study. When the size of the system decreases to a few nanometers, stability is not observed as a result of the large size. We theoretically examine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Theoretical investigations on the magnetic properties of CoZnO materials, using the Heisenberg exchange-coupling model, reported that the particles' size and shape play significant roles in controlling the magnetic behavior and magnetization phenomena [34]. The phase characteristics and optoelectronic applications of these materials were also discussed in terms of the diluted magnetic semiconducting systems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Theoretical investigations on the magnetic properties of CoZnO materials, using the Heisenberg exchange-coupling model, reported that the particles' size and shape play significant roles in controlling the magnetic behavior and magnetization phenomena [34]. The phase characteristics and optoelectronic applications of these materials were also discussed in terms of the diluted magnetic semiconducting systems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%